Odpowiedź :
Zadanie 1
a) 2 * (a + 5) = 2a + 2 * 5 = 2a + 10
b) -3 * (4 - 2b) = -3 * 4 - 3 * (-2b) = -12 + 6b
c) (7 - c) * 5 = 7 * 5 - 5c = 35 - 5c
d) (4d + 8) : 4 = 4d : 4 + 8 : 4 = d + 2
Zadanie 2
a) 9 + (2 - 6a) = 9 + 2 - 6a= 11 - 6a
b) - (6b + 1) = - 6b - 1
c) (9 + f) - (3f - 4) = 9 + f - 3f + 4 = 13 - 2f
a) 2 * (a + 5) = 2a + 2 * 5 = 2a + 10
b) -3 * (4 - 2b) = -3 * 4 - 3 * (-2b) = -12 + 6b
c) (7 - c) * 5 = 7 * 5 - 5c = 35 - 5c
d) (4d + 8) : 4 = 4d : 4 + 8 : 4 = d + 2
Zadanie 2
a) 9 + (2 - 6a) = 9 + 2 - 6a= 11 - 6a
b) - (6b + 1) = - 6b - 1
c) (9 + f) - (3f - 4) = 9 + f - 3f + 4 = 13 - 2f